A descriptive analysis of anglicisms used in Ecuadorian Magazines - Oviedo Zúñiga, Silvana Patricia (2011)
The theme of the following research is “A descriptive analysis of Anglicisms in Ecuadorian magazines” and its purpose is to research on the linguistic phenomenon of Anglicisms used in Ecuadorian magazines. This study was developed in the city of Quito. To work in this study, it was necessary to collect Anglicisms from various types of Ecuadorian magazines: cultural, scholarly and general interest “Sophia: Revista de filosofía, La Casa: Revista de la Casa de la Cultura Ecuatoriana Benjamín Carrión, Retos: Revista de Ciencias de la Administración y Economía, América Economía Ecuador, Estadio Coleccionable and Vistazo” respectively.